2020
DOI: 10.3762/bjnano.11.28
|View full text |Cite
|
Sign up to set email alerts
|

Brome mosaic virus-like particles as siRNA nanocarriers for biomedical purposes

Abstract: There is an increasing interest in the use of plant viruses as vehicles for anti-cancer therapy. In particular, the plant virus brome mosaic virus (BMV) and cowpea chlorotic mottle virus (CCMV) are novel potential nanocarriers for different therapies in nanomedicine. In this work, BMV and CCMV were loaded with a fluorophore and assayed on breast tumor cells. The viruses BMV and CCMV were internalized into breast tumor cells. Both viruses, BMV and CCMV, did not show cytotoxic effects on tumor cells in vitro. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 60 publications
0
31
0
2
Order By: Relevance
“…The use of a fluorescent labelling is necessary to detect the VLP's by confocal microscopy. In a previous work we demonstrated that the VLP's from BMV are able to be internalized with and without fluorophore in tumor cells, [42] as well other groups demonstrated the cell internalization VLP′s from BMV into bronchial epithelial cells [44] . Hepatocytes, fibroblasts and kidney cells showed abundant cell internalization as demonstrated by the green fluorescence of FITC.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…The use of a fluorescent labelling is necessary to detect the VLP's by confocal microscopy. In a previous work we demonstrated that the VLP's from BMV are able to be internalized with and without fluorophore in tumor cells, [42] as well other groups demonstrated the cell internalization VLP′s from BMV into bronchial epithelial cells [44] . Hepatocytes, fibroblasts and kidney cells showed abundant cell internalization as demonstrated by the green fluorescence of FITC.…”
Section: Resultsmentioning
confidence: 61%
“…Here, GALT has been effectively encapsulated in a VLP form BMV (Figures 3 and 4), preserving catalytic activity (Table 1). Virus‐like nanoparticles from the plant virus BMV seems to be a good candidate for the enzyme delivery because it shows a very low immunogenicity [42] …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations